Odpowiedź :
a) 2(x+4) = -3(2x-4)
2x + 8 = -6x + 12
2x + 6x = 12 - 8
8x = 4 /:8
[tex]x = \frac{4}{8}[/tex]
[tex]x = \frac{1}{2}[/tex]
b) [tex]\frac{2}{5}x + 10 = \frac{1}{5} - 2x[/tex] /*5
2x + 50 = 1 - 10x
2x + 10x = 1 - 50
12x = -49 /:12
x = [tex]- \frac{49}{12}[/tex]
[tex]x = -4\frac{1}{12}[/tex]
c) [tex]\frac{3}{7}x + 2 = -4x[/tex] /*7
3x + 14 - 28x
3x + 28x = -14
-31x = -14 /:(-31)
[tex]x = -\frac{14}{31}[/tex]
d) 12x-9 = -4(x+9)
12x - 9 = -4x - 36
12x + 4x = -36 + 9
16x = -27 /:16
[tex]x = -\frac{27}{16}[/tex]
[tex]x = -1\frac{11}{16}[/tex]
e) [tex]4x - 5 = \frac{1}{3}x + 4[/tex] /*3
[tex]12x - 15 = x +12[/tex]
[tex]12x -x = 12 + 15[/tex]
11x = 27 /:11
[tex]x = \frac{27}{11}[/tex]
[tex]x = 2\frac{5}{11}[/tex]
f) [tex]4x - 6 = \frac{3}{4}[/tex]
[tex]4x = \frac{3}{4} + 6[/tex]
[tex]4x = \frac{27}{4}[/tex] /:4
[tex]x = \frac{27}{16}[/tex]
[tex]x = 1\frac{11}{16}[/tex]
g) -4(x+5) = -7(2x-9)
-4x - 20 = -14x + 63
-4x + 14x = 63 + 20
10x = 83 /:10
x = [tex]\frac{83}{10}[/tex]
[tex]x = 8\frac{3}{10}[/tex]